Effects of different soccer stud configurations on knee kinematics and shoe-surface traction of sidestep cutting movement on natural grass - Sun, D.; Gu, Y.; Ruan, G.; Yang, L. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to inwstigate the effect of different stud configuration on knee joint kinematics of sidestep cutting movement on natural grass. A total of 14 amateur soccer players participated in the tests. Participants were asked to complete tasks of 45" sidestep cutting at the speed of 5.0M+-2m/s on natural grass. They selected soccer s h m with firm ground design (FG), artificial ground design (AG) and turf cleats (TF) randomly. During 45" cut, peak knee flexion (p less than 0.001) and abduction angles (p<0.001) of firm ground design (FG) were significantly greater than turf cleats (TF). FG also showed significant greater average required traction ratio compared with AG (p less than 0.001) and TF (p<0.001). Decreased knee flexion angles and increased knee abduction angles of firm ground design (FG) during cutting movemenents may increase risk of anterior cruciate ligament (Am) injury. Higher utilized traction of FG could produce mare grip which allows athletes to cutting and turning rapidly without skidding. However, higher utilized traction might lead to risk of slip resistance and foot fixation which might increase the load of lower limbs.